2016
DOI: 10.1515/geosc-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Will Distance to the Capital City Matter When Supplying New Cities in Egypt?

Abstract: Unlike other developing countries, the housing market in Egypt is characterized by densely populated urban areas in old cities and the peripheral urban agglomeration. In contrast, a high rate of vacancy along most of the new cities that have been established since the 1980s is seen. Regardless of such high rate of vacancies, still the variation in occupancy rates among those new cities is notable. Questions arising include: Does proximity to old cities or Greater Cairo affect the size of the population of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Around Caïro, desert cities such as 6th of October City, 10th of Ramadan City and New Cairo, amongst others, have been developed since the 1970s and 1980s [56]. This process has also gradually impacted Middle and Upper Egypt from the 1990s and 2000s onwards, with new towns being planned near Minya, Assiut and Qena, amongst others [57].…”
Section: Urban and Agricultural Land Dynamicsmentioning
confidence: 99%
“…Around Caïro, desert cities such as 6th of October City, 10th of Ramadan City and New Cairo, amongst others, have been developed since the 1970s and 1980s [56]. This process has also gradually impacted Middle and Upper Egypt from the 1990s and 2000s onwards, with new towns being planned near Minya, Assiut and Qena, amongst others [57].…”
Section: Urban and Agricultural Land Dynamicsmentioning
confidence: 99%
“…In Egypt, the distance between the neighbourhood and the capital city may influence individual choices, giving that their jobs or family members may live in the capital city (Greater Cairo). Hence, the distance to the capital city could play a role in selecting between neighbourhoods in different new cities based on how far they are from the capital (Ibrahim and Masoumi 2016). A deeper inquiry into the reason of "nice neighbourhood" for selecting housing location also revealed that the most significant variable that affects this factor is the "car ownership".…”
Section: Discussionmentioning
confidence: 99%
“…The second objective is to apply and test this framework using it to determine the urban growth and LST of 6th of October City as a case study of being one of the first new cities to be established in Egypt. Because the more the new city progresses, the more local infrastructure and facilities are planned and implemented [19].…”
Section: Introductionmentioning
confidence: 99%